Independent Board Terhadap Pengungkapan Akuntansi Manajemen Strategis: Peran Proprietary Cost & Cost Of Capital Sebagai Variabel Moderasi - Honggowati, Setianingtyas; Suhardjanto, Djoko; Probohudono, Agung Nur; Hapsari, Andi Asri (E-Jurnal Akuntansi; Vol 33 No 10 (2023)DO - 10.24843/EJA.2023.v33.i10.p19, 2023)
Information asymmetry, agency problems and disclosure are important aspects of modern capital markets. This research aims to measure the extent of Strategic Management Accounting (AMS) disclosure and examine the influence of the independent board on the level of AMS disclosure. This research uses proprietary cost and cost of capital as moderating variables. This research uses data from 545 manufacturing companies listed on the Indonesia Stock Exchange from 2016 - 2020. This research uses multiple linear regression with panel data to test the influence of independent boards on the level of AMS disclosure. In addition, this research uses Moderated Regression Analysis to test the role of proprietary costs and cost of capital as moderating variables. The research results show that independent boards have a positive effect on AMS disclosure when there is a trade-off between the benefits and costs of AMS reporting for shareholders. Keywords: Independent Boards; SMA Disclosure; Proprietary Cost; Cost of Capital